PENGELOLAAN KEUANGAN BISNIS ONLINE MENGGUNAKAN TELEPON PINTAR - Maulana, Sahdan; Fitrianingrum, Ayu; Damara, Abieza Satya; Quinta, Enno Astri; Sari, Evie Puspita; Hariputra, Kartiko; Mu’arief, M. Ilham; Zuti, Utari Ayuningrum; Raharjo, Taufik (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
The object of this community service is SME Dpp.bookstore. The purpose of this community service activity is to raise awareness of the importance of accounting for and equip skills in financial management or accounting with the Android-based "SME Accounting" application. This community service activity is in the form of direct assistance to BUMK managers. The result of this community service activity is an increase in understanding the importance of managing business financial administration and accounting by using the "SME Accounting" application. The obstacle faced is no evidence is collected for every transaction that occurs by the SME business owner Dpp. Bookstore.